A STUDY OF PROFESSIONAL ATTITUDE OF TEACHERS TRAINEES IN DIFFERENT TEACHER TRAINING INSTITUTIONS - Tyagi, Anjali; Jain, Vinod Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
Every individual have different attitude for same object, thing or work. Attitude plays big role to understand and experience batter things. People adopt different profession in respect to their interest and need. There are many professions available to every person and teaching is also a profession. Some teachers adopts teaching due to interest and some takes it as a job but teaching is really profession of interest because it gives chance to live student forever to learn new things. Hence researcher decided “To study of professional attitude of teachers teaching in different teacher training institutions”. For this purpose researcher taken two type of institutions which are government aided and self-financed teacher training institutions. Researcher taken 100 teachers of both type of institutions (50 male and 50 female) teachers. No significance difference found between governments aided and self-finance institutions teachers. No significance difference was found between male and female teachers of government aided and self-financed institutions.